Development of κ-Carrageenan Films Reinforced with Magnesium Oxide Nanoparticles for the Potential Treatment of Chronic Wounds: In Vitro and In Vivo Insights - Lesly Rodríguez-Vicens; Jorge L. Mejía-Méndez; Edgar R. López-Mena; Sergio A. Bernal-Chávez (Polysaccharides)
In this work, κ-carrageenan (κ-C) and polyethylene oxide (PEO) were utilized to synthesize polymeric films (κ-C-PEO). A 2k experimental design was employed to optimize the synthesis of κ-C-PEO systems by considering the content of κ-carrageenan, PEO, and glycerin and their influence on the mechanical features of the resultant films. The κ-C-PEO systems were robustly characterized by FTIR spectroscopy, thermogravimetric analyses, and scanning electron microscopy (SEM). Magnesium oxide nanoparticles (MgO-NPs) were utilized to load κ-C-PEO films as an efficient approach to enhance their biological performance. The activity of κ-C-PEO films was studied against Gram-negative bacteria through the Kirby–Bauer assay. Artemia salina nauplii were cultured to assess the possible toxicity of κ-C-PEO films. The results demonstrated that κ-C-PEO films were elongated with the heterogeneous distribution of MgO-NPs. The tensile strength, thickness, and swelling capacity of κ-C-PEO films were 129 kPa, 0.19 mm, and 52.01%, respectively. TGA and DTA analyses revealed that κ-C-PEO films are thermally stable structures presenting significant mass loss patterns at >200 °C. Treatment with κ-C-PEO films did not inhibit the growth of Escherichia coli nor Pseudomonas aeruginosa. Against A. salina nauplii, κ-C-PEO films did not decrease the survival rate nor compromise the morphology of the tested in vivo model. The retrieved data from this study expand the knowledge about integrating inorganic nanomaterials with polysaccharide-based structures and their possible application in treating chronic wounds. Even though this work provides innovative insights into the optimal design of bioactive structures, further approaches are required to improve the biological performance of the synthesized κ-C-PEO films.